Effects of the COVID-19 pandemic on the outcomes of HIV-exposed neonates: a Zimbabwean tertiary hospital experience - Hannah Gannon; Elizabeth Chappell; Deborah Ford; Diana M Gibb; Anesu Chimwaza; Ngoni Manika; Catherine J Wedderburn; Zivai Mupambireyi Nenguke; Frances M Cowan; Tom Gibb; Andrew Phillips; Angela Mushavi; et al. (BMC Pediatrics, 2024)
Abstract Introduction The COVID-19 pandemic has globally impacted health service access, delivery and resources. There are limited data regarding the impact on the prevention of mother to child transmission (PMTCT) service delivery in low-resource settings. Neotree ( www.neotree.org ) combines data collection, clinical decision support and education to improve care for neonates. Here we evaluate impacts of COVID-19 on care for HIV-exposed neonates. Methods Data on HIV-exposed neonates admitted to the neonatal unit (NNU) at Sally Mugabe Central Hospital, Zimbabwe, between 01/06/2019 and 31/12/2021 were analysed, with pandemic start defined as 21/03/2020 and periods of industrial action (doctors (September 2019-January 2020) and nurses (June 2020-September 2020)) included, resulting in modelling during six time periods: pre-doctors’ strike (baseline); doctors’ strike; post-doctors’ strike and pre-COVID; COVID and pre-nurses’ strike; nurses’ strike; post nurses’ strike. Interrupted time series models were used to explore changes in indicators over time. Results Of 8,333 neonates admitted to the NNU, 904 (11%) were HIV-exposed. Mothers of 706/765 (92%) HIV-exposed neonates reported receipt of antiretroviral therapy (ART) during pregnancy. Compared to the baseline period when average admissions were 78 per week (95% confidence interval (CI) 70–87), significantly fewer neonates were admitted during all subsequent periods until after the nurses’ strike, with the lowest average number during the nurses’ strike (28, 95% CI 23–34, p < 0.001). Across all time periods excluding the nurses strike, average mortality was 20% (95% CI 18–21), but rose to 34% (95% CI 25, 46) during the nurses’ strike. There was no evidence for heterogeneity (p > 0.22) in numbers of admissions or mortality by HIV exposure status. Fewer HIV-exposed neonates received a PCR test during the pandemic (23%) compared to the pre-pandemic periods (40%) (RR 0.59, 95% CI 0.41–0.84, p < 0.001). The proportion of HIV-exposed neonates who received antiretroviral prophylaxis during admission was high throughout, averaging between 84% and 95% in each time-period. Conclusion While antiretroviral prophylaxis for HIV-exposed neonates remained high throughout, concerning data on low admissions and increased mortality, similar in HIV-exposed and unexposed neonates, and reduced HIV testing, suggest some aspects of care may have been compromised due to indirect effects of the pandemic.